Effects of Patient Dose Reduction Efforts on Image Quality for Thoracic CT in A Moroccan Hospital - Saga, Z.; Rahmouni, A.; Belaroussi, L.; Talbi, M.; El Mansouri, M.; Rezzouk, A. (National Research and Innovation Agency, 2024)
Thoracic CT imaging is a strongly recommended means of medical imaging. It is accompanied by a high exposure to radiation due to the number of examinations carried out, which requires efforts to reduce the CT dose index (CTDI) while trying to preserve image quality. To this end, this study proposed the possibility of introducing two new imaging protocols for chest tomography. A 16-slice HITACHI SUPIA CT scanner and two phantoms were used to investigate CTDIvol and image quality; the first phantom was made of PMMA and the other of AAPM model 610. Three tube voltages were studied by varying the intensity of the tube current (mA): 120 kVp (120-160-210-230) mA, 100 kVp (160-200-240-290) mA, and 80 kVp (230-260-300-350) mA. The values for noise uniformity and accuracy, contrast-to-noise ratio (CNR), and spatial resolution (SR) were determined using IndoQCT c22a. 92 software. The first thoracic protocol proposed with 100 kVp compared to 120 kVp resulted in a 27.51 % reduction in CTDIvol, a 20 % increase in mA, and a 19.50 % increase in noise. The CNR showed a slight regression of 23.08 %. For the second scan procedure at 80 kVp, the CTDIvol was reduced by 53.32 %, while noise was increased by 53.95 %. There was no statistically significant difference in CNR and SR (p > 0.05) when kVp and mA were reduced compared to the routine protocol. It is suggested that it is possible to adopt two new acquisition protocols at 100 kVp and 80 kVp while reducing the patient exposure dose (CTDIvol) by 28 % and 54 % and taking into account the effect of varying these parameters on image quality. Their choices must be made by integrating and considering clinical issues and a good understanding of the pathophysiology and imaging results of the suspected condition. Consequently, radiologists and technicians should always take a part in improving imaging practices in such a way as to make more effective use of radiation.